Transcriptional regulation of DC fate specification. (May 2020) - Bosteels, Cédric; Scott, Charlotte L.
Highlights: Roles for IRF8, IRF4, NOTCH, ZEB2, KLF4 and TBet in cDC1 and cDC2 fate specification. Switch from +41 kb to +32 kb enhancer in IRF8 is required for cDC1 development. NFIL3 functions to inhibit ZEB2 enabling ID2 expression in cDC1s. cDC2 heterogeneity across tissues remains incompletely understood. Role of tissue microenvironment in cDC2 heterogeneity remains to be studied. Abstract: Dendritic cells function in the immune system to instruct adaptive immune cells to respond accordingly to different threats. While conventional dendritic cells can be subdivided into two main subtypes, termed cDC1s and cDC2s, it is clear that further heterogeneity exists within these subtypes, particularly for cDC2s. Understanding the signals involved in specifying each of these lineages and subtypes thereof is crucial to (i) enable us to determine their specific functions and (ii) put us in a position to be able to target these cells to promote or prevent a specific function in any given disease setting. Although we still have much to learn regarding the specification of these cells, here we review the most recent advances in our understanding of this and highlight some of the next questions for the future.